An unexpected case of lower lip benign Schwannoma: diagnosis, management and review of literature - Mona, Henam; Anand, Rishi; Sharma, Ankur (International Surgery Journal, 2023)
Schwannoma also known as neurinomas of verocay is a benign, slow growing, nerve sheath tumor arising from the Schwann cells of the nerve. Around 25-40% of the schwannoma arises from the soft tissues of head and neck areas. Out of which, only <1% arises from the oral cavity. The most common intra-oral site is the tongue and the least common site being the lips. Moreover, Schwannoma in the lower lip are excessively rare during childhood and adolescence. Due to its rarity in lower lip, it’s diagnosis is usually overlooked during the primary examination. Complete surgical excision of the tumor is the treatment of choice. Recurrence cases and malignant degeneration are extremely rare. Here, we reported a case of a 17 year old female with peripheral Schwannoma of the lower lip, presented to the Otorhinolaryngology department, Indira Gandhi Hospital, Dwarka, Delhi with complaints of painless swelling in the lower lip causing cosmetic deformity for the patient. She underwent complete enucleation of the mass and is being follow-up in the outpatient department.